Prognostic significance of the modified Glasgow Prognostic Score in NSCLC patients undergoing immune checkpoint inhibitor therapy: a meta-analysis - Wu, Jiaxuan; Wang, Haoyu; Yang, Ruiyuan; Liu, Dan (Frontiers in Oncology, 2024)
BackgroundThe modified Glasgow Prognosis Score (mGPS), which considers both inflammatory response and nutritional status, has been linked to the prognosis of various tumors. The relationship between mGPS and non-small cell lung cancer (NSCLC) patients receiving immune checkpoint inhibitors (ICIs) is still a subject of debate. This meta-analysis aims to comprehensively assess the association between mGPS and survival in NSCLC treated with ICIs.MethodsA thorough review of studies from PubMed, Web of Science, Scopus, and Embase was conducted up to June 4, 2024. Fixed-effect or random-effect models were employed, combining hazard ratios (HRs) and 95% confidence intervals (CI), to assess the prognostic value of mGPS for OS and PFS in patients with NSCLC receiving immunotherapy.ResultsA total of 1,022 patients from 11 studies were recruited. Combined results showed that mGPS elevation was significantly associated with poor OS (HR = 1.63, 95%CI: 1.42-1.87, P < 0.01) and PFS (HR = 1.71, 95%CI: 1.31-2.24, P < 0.01). Subgroup analysis and sensitivity analysis further determined the predictive effect of elevated mGPS on OS and PFS deterioration in NSCLC patients receiving immunotherapy.ConclusionmGPS can be used as a good noninvasive biomarker to demonstrate prognostic and clinical significance in patients with NSCLC undergoing immunotherapy.Systematic review registrationhttp://www.crd.york.ac.uk/prospero/ PROSPERO, identifier CRD42023432661.